THE CORRELATION BETWEEN STUDENTS’ READING BEHAVIOR AND THEIR READING COMPREHENSION - Polii, Kevin Albert; Syahputra, Idham (State Islamic University of Sultan Syarif Kasim Riau, 2025)
The main focus of this research was to examine if there is a significant correlation between reading habit and reading comprehension at the Eight Gradeof Junior High School Telekomunikasi Pekanbaru. The researcher using quantitative research, This research uses correlational research. In conducting the research, the sample of this research are 21 students. The subject of this research is the eight grade students at Junior High School Telekomunikasi Pekanbaru, the technique sampling that was used simple random sampling. In collecting the data, There were two kinds of instruments that were questionare and test. The technique of analyzing data was using pearson product moment correlatin and it was eased by using SPSS 20.0 program. Based on the data analysis, the researcher conclude that the level of students’ Reading Habits of Eight Grade of Junior High School Telekomunikasi Pekanbaru is Excellent Level. The level of students’ Reading Comprehension of Eight Grade of Junior High School Telekomunikasi Pekanbaru is Good Level. It can indicates a sig.value was 0.000. it was bigger than 0.05 (sig(2 tailed)<0,05 ). The result the sig. (2-tailed) is 0.000, it can be conclude that, Ha was accepted and H0 was rejected. Based on the overall analysis above, the hypotheses H0 was accepted and Ha was rejected. So, it can be conclude that “There is a Significant Correlation between Students’ Reading Habits and Their Students’ Reading Comprehension of Eight Grade of Junior High School Telekomunikasi Pekanbaru”.